Practice skills in social work and welfare more than just common sense - Maidment, Jane (London New York Routledge Taylor & Francis Group, 2023)
Practice Skills in Social Work and Welfare has established itself as the essential text to prepare students for the wide-ranging challenges they will face in today's human service sector. This new fourth edition continues the text's core strength of connecting theory with practical examples to build the reader's confidence and expertise in key areas of practice. Part I outlines the critical social work and strengths-based practices that underpin the book's approach and provides the context for learning practice skills in a group setting, during community development projects and with individuals and families. Part II focuses on developing effective relationships with service users, illustrating through realistic scenarios how social work and human service practitioners can apply their practice skills in a range of settings. In Part III the essential elements of client assessment are explored, including risk assessment and cross-cultural perspectives. Issues surrounding intervention are examined in Part IV from working with families and groups to challenging constructively and safely, while research, evaluation and facilitating closure are covered in the final part. This fourth edition is fully revised and updated, and features new material on working with Pasifika communities, LGBTQI+ service users and ethics in practice"--
Includes bibliographical references and index.
Keywords: Public welfare -- Australia; Public welfare -- New Zealand; Social service -- Australia; Social service -- New Zealand